SIMULATION OF IRON CORROSION IN LEAD-MAGNESIUM EUTECTIC (LME) USING OXYGEN INHIBITOR - Umi Sa'adah; Artoto Arkundato; Moh. Hasan (Jurnal Sains Materi Indonesia, 2020)
SIMULATION OF IRON CORROSION IN LEAD-MAGNESIUM EUTECTIC (LME) USING OXYGEN INHIBITOR. Lead-magnesium (Pb-Mg) is a metal that considered to have potential as a coolant raw material in the heat transfer system of nuclear reactors. However, the coolant in the form of Pb-Mg eutectic is corrosive to structured materials (eg steel cladding) used in reactors. In this research, steel material is represented by pure iron to simplify the simulation and calculation. This research aims to determine the effect of temperature on iron corrosion and the effect of adding oxygen as an inhibitor to reduce the iron corrosion rate in LME. In this study, corrosion was observed by looking at (coefficient) the diffusion of iron atoms into LME. A large iron diffusion coefficient represents high iron corrosion. To see inhibition effectivity with oxygen, the most effective oxygen concentration that can reduce the iron diffusion coefficient is searched. Simulations of iron corrosion and inhibition are performed using molecular dynamics simulation. The result of this research showed that oxygen concentration mixed into LME for effective inhibition of iron corrosion was in the range of 0.125 wt% - 0.135 wt% (for temperatures of 973K). Thus, oxygen is believed that able to inhibit iron corrosion in Pb-Mg eutectic up to 98.44%